(untitled) (Bangladesh Journal of Neuroscience, 2015)
Introduction: Short segment pedicle screw fixation is a popular procedure for treating unstable thoracolumbar burst fracture. But due to lack of adequate neurological improvement, progressive kyphosis and hardware failure- the efficacy of different methods remain debatable. Method : 50 patients with isolated thoracolumbar burst fractures were treated by short segment pedicle screw fixation and transforaminal thoracolumbar inter body fusion (TLIF) between January 2010 to December 2013. All patients were followed up for a minimum 2 years. Demographic data, Neurological improvement (Frankel) grade and Hardware failure related complication were evaluated. Results: All patients recovered with solid bony fusion by inter vertebral bone graft and pedicle screw without complications like misplacement of screw, nerve or vessel lesion or hardware failure. The post-operative radiographic demonstration reveals- good fracture reduction and it was well maintained until the bone graft fusion. Neurological recovery of the one to three Frankel grade was seen in 42 patients with partial neurological deficit. Among the 30 patients 3 grade improvements was seen in 4 patients, 2 grade of improvement was observed in 20 patients and 1 grade of improvement was found in 18 patients. 3 patients with Franke-D on admission showed no improvement. 5 patients with no paraplegia/hemiplegia on admission remained neurological intact. Conclusion: Posterior short segment pedicle fixation in conjunction with TLIF seems to be a feasible option in the management of selected thoracolumbar burst fracture with good neurological improvement. Bangladesh Journal of Neuroscience 2015; Vol. 31 (1): 30-33